Perceptions of Maritime Faculty of the University of Saint Anthony on the Shift of Traditional to Online Instruction - Estrella Arroyo; Christopher A Britanico (Sekolah Tinggi Maritim Yogyakarta, 2021)
This study focused on the perceptions of Maritime faculty of the University of Saint Anthony, Iriga City Philippines, on the shift of traditional to online instruction since the pandemic in March 2020 to the present.It is a purely qualitative study, a case study to specific, that used coding as its method to interpret and analyze the data gathered from unstructured interviews of the selected faculty of the Maritime department. Further, the study identified the experiences and challenges that confronted the faculty members; thus, enabled the researchers to arrive at conclusions and render recommendations. The findings of the study showed that Maritime faculty experiences on online instruction were deeply rooted on practicality and accessibility. It is both refreshing and difficult to do accordingly. The challenges were mostly tied to resources and investments used by the faculty during online interaction. This study shall become a basis for the implementation of new policies in the department in terms of faculty development, materials development and formulation of teaching strategies.